2012
DOI: 10.3109/10715762.2012.692786
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Chinese green tea on cigarette smoke-induced up-regulation of airway neutrophil elastase and matrix metalloproteinase-12 via antioxidant activity

Abstract: Our recent study has indicated that Chinese green tea (Lung Chen), in which epigallocatechin-3-gallate (EGCG) accounts for 60% of catechins, protected cigarette smoke-induced lung injury. We now hypothesized that Lung Chen tea may also have potential effect on lung oxidative stress and proteases/anti-proteases in a smoking rat model. Sprague-Dawley rats were exposed to either sham air (SA) or 4% cigarette smoke (CS) plus 2% Lung Chen tea or water by oral gavage. Serine proteases, matrix metalloproteinases (MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…This finding led us to investigate the role of SLPI in healthy mucosa of non-HNSCC patients and to correlate SLPI expression with smoking habits. In accordance with the data obtained in a rat model (18), we indeed showed that moderate/strong SLPI expression was mostly found in patients with smoking habits. In HNSCC, it is well documented that HPV-driven carcinogenesis occurs in younger patients when compared to patients with alcohol/tobacco-driven carcinogenesis (4,17).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding led us to investigate the role of SLPI in healthy mucosa of non-HNSCC patients and to correlate SLPI expression with smoking habits. In accordance with the data obtained in a rat model (18), we indeed showed that moderate/strong SLPI expression was mostly found in patients with smoking habits. In HNSCC, it is well documented that HPV-driven carcinogenesis occurs in younger patients when compared to patients with alcohol/tobacco-driven carcinogenesis (4,17).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Chan et al (18) showed that total neutrophil elastase concentration and activity as well as SLPI activity was increased following exposure to cigarette smoke. This finding led us to investigate the role of SLPI in healthy mucosa of non-HNSCC patients and to correlate SLPI expression with smoking habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al [57, 59] treated Sprague-Dawley rats with 2% Lung Chen Tea, a Chinese green tea, in the presence and absence of smoke for 56 days. Lung Chen Tea (2%) with the largest amount of EGCG was found to alter oxidative stress in the serum and lungs in the smoke-exposed group and protect against smoke-induced lung damage as determined by histological and morphometric analyses [57].…”
Section: Green Tea Modulates Smoke Related Diseases or Damagementioning
confidence: 99%
“…Lung Chen Tea (2%) with the largest amount of EGCG was found to alter oxidative stress in the serum and lungs in the smoke-exposed group and protect against smoke-induced lung damage as determined by histological and morphometric analyses [57]. Concomitantly, 2% Lung Chen Tea may also help to prevent the smoke-induced up-regulation of matrix metalloproteinase-12 (MMP12) activity, leading to a reduction in ROS [59]. Yang et al reported that catechins reduced oxidative stress by reducing the Bax/Bcl-2 ratio and preserving HSP70 chaperone protein expression in the lung of study animals [57].…”
Section: Green Tea Modulates Smoke Related Diseases or Damagementioning
confidence: 99%